Teorema de Tales: uma abordagem usando anamorfismos - Silva, Jonathan de Aquino da (2018)
The Flat Euclidian Geometry is a gigantic field and it is possible to have a very wide work with its concepts, since the more basic until the more sophisticated, but, the study of Geometry on the basic education leave a little to be desired. From the moment that study Geometry on the school and, being aware that Maths’ formulas doesn’t matter without a understanding of what is studying, this dissertation aimed search on didatic books, how is done the study of Thales’ Theorem, its demonstrations and applications, creating a alternative proposal based on anamorphisms study and its relation with the Theorem. The application of the alternative proposal may cause the Tales Theorem to be perceived in situations where the students did not expect and the creation of the anamorphisms caused the students’ creative spirit and teamwork to come to the surface as they learned more about or Tales Theorem.